2017
DOI: 10.3892/ol.2017.7687
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram oxalate inhibits proliferation and migration and induces apoptosis in non-small cell lung cancer cells

Abstract: Abstract. Population-based cohort studies have revealed that neuroleptic medications are associated with a reduced cancer risk. Recent studies have demonstrated that selective serotonin reuptake inhibitors (SSRIs) have an antiproliferative or cytotoxic effect on certain cancer types. Known as a superior SSRI, escitalopram oxalate exhibits favorable tolerability with generally mild and temporary adverse events. The present study aimed to examine the effects of escitalopram oxalate on non-small cell lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Besides the COX-2dependent mechanism, SSRIs could activate the AMPK/mTOR pathway by increasing the phosphorylation of AMPK and blocking the phosphorylation of mTOR phosphorylation, thus inducing autophagic cell death in various cancer cells (21,44,45), and enhance the sensitivity of several chemotherapy drugs on colon cancer cells (46,47). Second, SSRIs were reported to induce apoptosis, inhibit DNA repair, and reduce the metastatic potential through NF-kB pathway in lung cancer cells (22,48). Third, SSRIs could yield additional antiplatelet effects in patients with antecedent treatment (19), which might also enhance the anticancer effect of aspirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the COX-2dependent mechanism, SSRIs could activate the AMPK/mTOR pathway by increasing the phosphorylation of AMPK and blocking the phosphorylation of mTOR phosphorylation, thus inducing autophagic cell death in various cancer cells (21,44,45), and enhance the sensitivity of several chemotherapy drugs on colon cancer cells (46,47). Second, SSRIs were reported to induce apoptosis, inhibit DNA repair, and reduce the metastatic potential through NF-kB pathway in lung cancer cells (22,48). Third, SSRIs could yield additional antiplatelet effects in patients with antecedent treatment (19), which might also enhance the anticancer effect of aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental studies reported that SSRIs had an antiplatelet effect (19) and could downregulate the expression of COX-2 (20). Furthermore, SSRIs exert an antitumor effect through COX-2 by inducing autophagic cell death via adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR) pathway (21) and inducing apoptosis through nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway (22). Based on the evidence above, it is biologically plausible for the combination use of SSRIs and aspirin to achieve an enhanced effect on CRC prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Second, fluoxetine and sertraline could inhibit the proliferation of colon cancer cells by activating the JNK-c-Jun pathway [ 35 , 36 ]. Third, fluoxetine and escitalopram were also reported to inhibit the expression of proteins involved in the DNA repair mechanism and to suppress the NF-κB signaling pathway to reduce the cancer cell metastatic potential [ 37 , 38 ]. Fourth, fluoxetine and sertraline could elevate the phosphorylation of AMPK and block downstream mTOR pathway, resulting in autophagic cell death in various cancer cells [ 39 , 40 , 41 ], and enhance the sensitivity of several chemotherapy drugs on colon cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its dysregulation is an essential reason for HCC progression (Fabregat, 2009). Apoptosis is managed by numerous signaling pathways along with caspases protease (Yuan et al, 2018). downregulation or loss of caspase-3 expression is in cancerous cell is mostly accompanied by resistance to apoptosis as well as chemotherapy in several kinds of tumors (Kolenko et al, 1999).…”
Section: Effects Of Endo And/or Benzo On Tumor Marker and Apoptotic Bmentioning
confidence: 99%